Refleksi Budaya Etnis Tionghoa dalam Kesenian Barongsai di Kota Singkawang - Putra, Zakarias Aria Widyatama; Wulanda, Gigih Alfajar Novra (Besaung : Jurnal Seni Desain dan Budaya, 2024)
The lion dance is a form of ethnic Chinese culture with a beautiful variety of motion and visual ornaments.  The purpose of this research is to serve as a reminder of cultural preservation and inheritance. The primary reflection resources paired with Feldman's art criticism method include a historical overview, performance dynamics, ritual/celebration procedures, and cultural heritage. This study also provides a glimpse into and description of ethnic Chinese's effort to express cultural arts following a time of prejudice. The dissection is carried out utilising descriptive qualitative methodologies, with data collected through participant observation, in-depth interviews, and documentation. Triangulation of sources with ethnomusicologists validates the data analysed using an inter-academic model. Cultural reflection produced by Barongsai arts for ethnic Chinese includes reminders and awareness of evaluative materials related to the struggle for discrimination in the historical context, entertainment and sports functions in the context of performance dynamics, meanings and symbols of happy and sad expressions in the context of ritual / celebration processes, and sorting out incoming outside cultures for the younger generation in the context of cultura. It is critical and beneficial that the findings of this study serve as a vehicle and platform for future attempts to maintain and enhance the Barongsai art form. In addition, there needs to be support between elements of the ethnic Chinese community and the government so that the art of Barongsai can be preserved and developed in the future.